Intertemporal Distribution, Suffciency, and the Social Cost of Carbon - Martin C. Hänsel; Martin F. Quaas (Ecological Economics, 2018)
We explore how the intertemporal distribution of well-being affects the social cost of carbon. In contrast to the literature that studies parameters of a particular social welfare function, such as the discount rate, we shift the focus and directly assume a parametric form for the intertemporal distribution of well-being. This has the advantage of avoiding explicit discounting choices, which has initiated much debate. Specifically, we consider a set of intertemporal distributions that reach a pre-specified steady-state level of "sufficient" well-being, or equivalently, after a pre-specified "end-of-growth horizon". We numerically illustrate our results in DICE and find that the social cost of carbon increases over-proportionally with the sufficiency level of well-being. While the social cost of carbon in 2015 is US 7 if the sufficiency level is four-fold the present level, it is US 30 if the sufficiency level is 15-fold and US 100 if the sufficiency level is 26-fold the present level. This shows in a transparent way how conceptions of intergenerational distributive justice drive the social cost of carbon.
Keywords: Q01; Q54; H21; C61; D31; D91; 330; climate change; social cost of carbon; optimal tax; DICE; optimal growth; sustainability; social welfare function; discounting